PENGARUH PENAMBAHAN MOBILISASI SARAF MEDIANUS SETELAH DIBERIKAN ULTRASOUND THERAPY PADA PENURUNAN NILAI NYERI CARPAL TUNNEL SYNDROME - Ruhana F Mujahad (NHM PRESS, 2019)
Carpal tunnel syndrome can result fromexcessive movement in the joints can lead tocarpal synovial joints increases and tapping themedian nerve in the carpal tunnel so that itappears one of the various complaints of pain. Toreduce the pain of carpal tunnel syndrome can begiven additional mobilization of the median nerveafter ultrasound therapy which have beencommonly used in physiotherapy services in manyhospitals. To determine the effect of the mediannerve mobilization after ultrasound therapy todecrease the value of the pain of carpal tunnelsyndrome. This research uses quasi experimentalapproach, research design pre and post test twogroups design. The first group of elderly givenultrasound therapy and the second group wasgiven the mobilization of the median nerve. Thenumber of samples in this study of 12 samples,sample taker technique by purposive samplingtechnique that uses existing population criteria ofinclusion and exclusion. In the study the effect oftest used Wilcoxon test and Mann Whitney testdifferent influences. Wilcoxon test results on themedian nerve mobilization group after the additionof ultrasound therapy asymp values obtained. Sig(2-tailed) = 0.026 indicates the value of p <0.05there is the influence of pain using the VAS valuereduction in carpal tunnel syndrome. From theresults of Mann Whitney test result Sig (2-tailed) =0.183 (Asymp. Sig (2-tailed)> 0.05), which meansthere is no significant difference in both groups, inthe sense that both have effects in lowering painCarpal Tunnel Syndrome. No effect of the mediannerve mobilization after ultrasound therapy todecrease the value of the pain of carpal tunnelsyndrome.